Beneficence and non-maleficence: confidentiality and carers in psychiatry. (17th December 2015) - Casey, P.
Abstract : The editorial considers how psychiatrists can deal with concerns relating to confidentiality that are prominent in patients and their carers. Confidentiality is paramount but there are situations when it can be breached. Some of these relate to emergency situations, others apply in less compelling circumstances. The ethical principles relating to confidentiality will be discussed. An assessment of capacity is central to the person's ability to consent/refuse information gathering or disclosure. Even when capacity is present, there are strategies that psychiatrists can use to respect patient autonomy while meeting the needs of carers. The possibility of training in negotiating these should be considered, as should advance directives.